Empowerment Leprosy Sufferer Patients in Kupang City - Ramses Victor Elim (Jurusan Peternakan Politeknik Pertanian Negeri Kupang, 2017)
Leprosy is one of the infectious diseases that belong to a neglected disease (Neglected Tropical Diseases). The disease is often a very complex problem in terms of both medical and extending to the social, economic and cultural. Bernad Nau and Yunnus Lassa are two leprosy sufferer patients. Since 2012, Bernad Nau and Yunus Lassa with the helping of his family, concentrating efforts of breedlocal pork. Fattening and breeding pigs traditionally run up to face many hurdles. But with the advent of slavery activities through the provision of good health assistance package (leaflets, counseling and early detection of leprosy simulation, leprosy equipment self-care and good hand washing) or the support of the module and tools of the pig breeding (cages, feed, and pork), knowledge and their skills increase. This impact on the improvement of their well-being through improved health and economy.Keywords : Economy, Empowerment, Improvement, LeprosyÂ